Genotyping by Induced Förster Resonance Energy Transfer (iFRET) Mechanism and Simultaneous Mutation Scanning. Issue 4 (5th March 2013) - Masojć, Bartłomiej; Górski, Bohdan; van de Wetering, Thierry; Dębniak, Tadeusz; Cybulski, Cezary; Jakubowska, Anna; Mędrek, Krzysztof; Rudnicka, Helena; Dwight, Zachary Lawrence; Lubiński, Jan
Abstract : In this article we present a single step genotyping technique based on induced Förster Resonance Energy Transfer (iFRET) mechanism in conjunction with simultaneous mutation scanning. We show that it is a useful and cost‐effective method for detection of both germline and somatic mutations. ABSTRACT: Multiple genotyping techniques were developed on the basis of real‐time PCR. In this article, we present a genotyping technique extending the induced Förster resonance energy transfer (iFRET) mechanism in conjunction with simultaneous mutation scanning. Rapid, asymmetric PCR was performed with SYTO9, polymerase lacking 5′ → 3′ exonuclease activity, two primers, and a probe labeled with 6‐Carboxy‐X‐rhodamine. Six primers and probe sets were designed to detect germline mutations in BRCA1, a singular polymorphism in CCND1 and somatic mutations in KRAS and BRAF genes. The validation set consisted of 140 archival DNA samples from patients with previously confirmed BRCA1 mutation and 42 archival formalin‐fixed and paraffin‐embedded tissues from patients with colorectal cancer or malignant melanoma. BRCA1 and CCND1 genotyping by iFRET probe showed 100% agreement with Sanger sequencing and other validated methods. A combination of iFRET and high‐resolution melting analysis (HRMA) detected a spectrum of six different mutations in the KRAS gene and three different mutations in the BRAF gene. Due to an allele enrichment effect, the sensitivity of mutation detection of iFRET–HRMA genotyping and sequencing of iFRET–HRMA PCR products was significant, increasing from 1.5% to 6.2%, respectively. The technique presented in this article is a useful and cost‐effective method for the detection of both germline and somatic mutations.